Hiring for diversity : the guide to building an inclusive and equitable organization - Woods, Arthur (Entrepreneur); Tharakan, Susanna (John Wiley & Sons, Inc., 2021)
"Business leaders finally have an appetite and urgency for driving diversity through their hiring practices, but there is significant lack in the strategies and resources to do so. Hiring for Diversity answers the need with the first comprehensive roadmap for diversity hiring. Based on Mathison's research-backed Equal Hiring Index and partnership with leading employers like Accenture and Wiley, the book provides the most cutting-edge examples of the policies and practices for inclusive hiring and gives leaders actionable resources for bringing the strategy to life. This book will address many low-hanging fruits that organizations can tackle to quickly improve their entire talent strategy and advance diversity hiring. It will also take a deep dive into specific areas and detail the steps needed to take to improve inclusivity (i.e., company website, job descriptions, candidate screening process, candidate engagement, job offer processes, etc.). The book will be impactful for recruiters, hiring managers, and organizational leaders alike"--